Table of Content - - (Journal of Islamic Sciences, 2023)
Table of Content: 1. Supply contracts, A comparative jurisprudential study Mrs. Abrar Rizq Allah Alsulami 2. The disagreement reasons about belief in predestination between Ahl Al-Sunnah Wa’l-Jama’ah and those who oppose them (review& study) Mr. Saad Ibrahim Abdullah Al Ahmed 3. Ibn Al-Zaghuni’s approach to his jurisprudential choices - prostration of forgetfulness and voluntary prayer chapter as a sample Mrs. Abeer Farhan Hasan, Prof. Hussain Mualwi Al-Shahrani 4. Analytical study of Al-Hawi’s book, by Imam Abi Al-Hassan Ali bin Mohammed Al-Basri, Al-Mawardi Al-Shafei, 450 H [From the Book of Hunting and Carcasses to the Book of swearing] Model Mr. Abdullah Ahmed Al-Zubaidi 5. Preservation of blessings and their disappearance in The Holy Quran Dr. Larbi Ben Mohamed Lakhnig